Post-abortion septic pelvic thrombophlebitis with right ovarian vein thrombosis complicated by septic pulmonary emboli - Khurram, Muhammad; Ahmad, Arslan; Mustafa, Sara; Anjum, Nida (Journal of Rawalpindi Medical College, 2026)
Septic pelvic thrombophlebitis (SPT) is an uncommon but important cause of persistent fever after delivery or gynaecological procedures1. Anticoagulation and parenteral antibiotics are the main treatment goals for ovarian vein thrombosis.2 Ovarian vein thrombosis (OVT) may complicate and lead to septic pulmonary embolism (SPE).3A woman in her early 20s presented with high-grade fever and right iliac fossa pain seven days after an induced abortion. Her fever persisted despite 72 hours of broad-spectrum intravenous antibiotics. Contrast-enhanced abdominopelvic computed tomography (CT) revealed a right OVT. Subsequent CT pulmonary angiography confirmed multiple peripheral, partly cavitating nodules consistent with SPE. She was successfully treated with optimized antimicrobial therapy and therapeutic anticoagulation. Fever abated, and interval imaging confirmed thrombus regression. She completed a three-month course of anticoagulation and remained well at follow-up with radiological resolution of pulmonary lesions. SPT should be suspected when postpartum or post-abortion fever fails to respond to adequate antibiotics. Prompt diagnosis with cross-sectional imaging and combined antimicrobial-anticoagulant therapy are essential to prevent complications and ensure a good outcome. Keywords: Ovarian Vein; Thrombophlebitis; Ovarian Venous Thrombosis; Septic Pulmonary Embolism; Puerperal Disorders.